2015
DOI: 10.1093/mnras/stv522
|View full text |Cite
|
Sign up to set email alerts
|

The chemical evolution of local star-forming galaxies: radial profiles of ISM metallicity, gas mass, and stellar mass and constraints on galactic accretion and winds

Abstract: The radially averaged metallicity distribution of the ISM and the young stellar population of a sample of 20 disk galaxies is investigated by means of an analytical chemical evolution model which assumes constant ratios of galactic wind mass loss and accretion mass gain to star formation rate. Based on this model the observed metallicities and their gradients can be described surprisingly well by the radially averaged distribution of the ratio of stellar mass to ISM gas mass. The comparison between observed an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(113 citation statements)
references
References 79 publications
8
102
0
1
Order By: Relevance
“…We adopt the general solution for these simple models derived by Kudritzki et al (2015) (hereafter K15) and relating the oxygen mass fraction O m (defined as the mass fraction of oxygen in the ISM: O m = M O /M gas ) and the gas fraction f gas :…”
Section: Implications For Galaxy Assembly and Evolutionmentioning
confidence: 99%
“…We adopt the general solution for these simple models derived by Kudritzki et al (2015) (hereafter K15) and relating the oxygen mass fraction O m (defined as the mass fraction of oxygen in the ISM: O m = M O /M gas ) and the gas fraction f gas :…”
Section: Implications For Galaxy Assembly and Evolutionmentioning
confidence: 99%
“…According to Kudritzki et al (2015), the ratio y/(1 − R) can be empirically determined from the fact that the metallicity of the young stellar population in the solar neighborhood is solar, with a mass fraction Z e = 0.014 (Nieva & Przybilla 2012). With a stellar-to-gas mass column density of 4.48 in the solar neighborhood (Wolfire et al 2003;Bovy & Rix 2013) one then obtains y/(1 − R) = 0.0082 = 0.59 Z e with an uncertainty of 15% dominated by the 0.05 dex uncertainty of the metallicity determination of the young population.…”
Section: Metallicity Measurementsmentioning
confidence: 99%
“…The latter manifests itself as the flattening of the (O/H) gradient at large radial distances R, mostly observed in galaxies which experience or have experienced a strong interaction (Werk, Putman, Meurer et al 2011;Zasov, Saburova, Katkov et al 2015). A comparison of y ef f and y o has been used by different authors to clarify the degree of difference of evolution from the closed-box model and to specify the processes which are responsible for the metal abundance besides the star formation and gas consumption (see f.e, Zahid, Dima, Kudritzki et al 2014;Kudritzki, Ho, Schruba et al 2015;Ascasibar, Gavilán, Pinto et al 2015).…”
Section: Yieldmentioning
confidence: 99%
“…Note, however, that the accretion and wind can in principle be disentangled (see Kudritzki, Ho, Schruba et al 2015). Although the results remain model dependent Kudritzki, Ho, Schruba et al (2015) demonstrated that the role of gas inflow/outflow may be different for different spiral galaxies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation